Analysis on the importance of entrepreneurship based on literature in Spanish from the Austrian school - Pava, Andrés; Chavarro Miranda, Fernando; Natalia Báez Gaona, Laura; Lorena Quincho Moreno, Yuri (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2024)
The Austrian school, based on methodological individualism, is connected with entrepreneurship due to the business function that human beings develop with their own means, or with capital from third parties. Therefore, this article analyzes the methods and elements of entrepreneurship in order to give a different perspective on it based on the capabilities of people in relation to their environment, since it was evidenced that there is not enough research on the subject considering the literature in Spanish language. The descriptive research methodology was used, with a qualitative approach, making a documentary review of authors in Spanish language; subsequently, a set of procedures interpreted from praxeology and methodological individualism were determined, as well as principles such as innovation, subjective value, entrepreneurship, catallactics, human action, being the bases for the creation of a successful business idea.